Peran Guru Ngaji dalam Meningkatkan Kemampuan Membaca Al-Qur’an melalui Metode Sorogan di Kampung Hanjuang Cisarua Bogor - Sudrajat, Muhammad Akbar; Gustiawati, Syarifah; Angelina, Putri Ria (Lembaga Yasin AlSys, 2023)
Basically the role of the Qur’an teacher in Hanjuang village is as a figure who is expected to be able to provide solutions to problems in society and as a guide for matters of the hereafter, especially in teaching the Qur'an. Reading the Al-Qur'an needs to be developed and needs to be taught among the Muslim community from children to adults. Therefore it is very necessary to have an education and teaching regarding methods and ways of understanding reading the Qur'an, especially the teacher's role in improving the ability to read the Qur'an. This study aims to describe the role of the Qur’an teacher in improving the ability to read the Qur’an, the implementation of the sorogan method in reading the Qur’an and the results of implementing the sorogan method in improving the ability to read the Qur’an in the village of Hanjuang Cisarua, Bogor Regency. The research method used is a qualitative method with a descriptive approach. The results of this study indicate that the Qur’an teacher in Kampung Hanjuang in improving children's ability to read the Qur’an has been able to carry out their role well because judging from the results of research that has been conducted, the Qur’an teachers have done many things in the learning process. The process of carrying out reading the Qur'an using the sorogan method every child gets the opportunity to face and learn directly with the teacher. The results of learning using the sorogan method in improving the ability to read the Qur’an, namely experiencing an increase in learning to read the Qur’an.